1975
DOI: 10.1203/00006450-197506000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Hemopexin Synthesis in Vitro by Human Fetal Tissues

Abstract: ExtractSerum concentrations of hemopexin, transferrin, and albumin were measured for 12 fetuses between 14 and 36 weeks of gestational age. Hemopexin levels ranged from 7 to 64 pg/ml, transferrin levels ranged from 280 to 928 pg/ml, and albumin levels ranged from 13 to 59 mg/ml. In general, the serum concentrations of these three proteins increased with advancing gestation.Placenta, thymus, and colon did not incorporate 14C-labeled amino acids into hemopexin, transferrin, or albumin. By contrast, radioimmune p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Finding a reduction in fetal plasma hemopexin in FGR suggests that most of the circulating levels have been depleted through chaperoning fetal heme to the maternal liver. Fetal plasma hemopexin levels are normally lower than adult levels as a result of the shorter half-life of fetal erythrocytes compared with adult erythrocytes and a greater need for heme detoxification of the fetal circulation (44). A further reduction of hemopexin in FGR fetal plasma suggests an even higher in vivo heme load in this disease.…”
Section: Elevated Fhbf In the Fetoplacental Circulation And Heme Handmentioning
confidence: 98%
“…Finding a reduction in fetal plasma hemopexin in FGR suggests that most of the circulating levels have been depleted through chaperoning fetal heme to the maternal liver. Fetal plasma hemopexin levels are normally lower than adult levels as a result of the shorter half-life of fetal erythrocytes compared with adult erythrocytes and a greater need for heme detoxification of the fetal circulation (44). A further reduction of hemopexin in FGR fetal plasma suggests an even higher in vivo heme load in this disease.…”
Section: Elevated Fhbf In the Fetoplacental Circulation And Heme Handmentioning
confidence: 98%
“…which are both abundantly expressed in decidua and the yolk sac (Choy et al, 1989;Thomas et al, 1989), and ceruloplasmin, which is equivalently expressed in fetal liver and lung tissue (Fleming & Gitlin, 1990). The temporal pattern of hemopexin gene expression in the liver is consistent with the observed fetal serum levels of hemopexin in human, rabbit, and chicken (Muller-Eberhard et al, 1975;Ross et al, 1971;Grieniger et al, 1986). In addition, previous clinical studies have indicated that serum hemopexin levels increase by 10-100-fold from fetal to adult life (Hanstein & Muller-Eberhard, 1968).…”
Section: Discussionmentioning
confidence: 64%